Hole's human anatomy & psychology - Shier, David (McGraw-Hill, 2007)
This new edition updates a great A&P classic while offering greater efficiencies to the user. The 11th edition of Hole also offers never before technology that combined with the text offer users an incredible Course Solution! Technology like Anatomy and Physiology Revealed and ARIS (Assessment, Review, and Instruction System), a complete electronic homework and course management system bring unprecedented opportunities to the classroom whether on campus or at home!